Contra Fatalism and Apatheticsm in Doing Theology: Embracing COVID-19 Pandemic with Theodicy- Preventive Approach - Rumbay, Christar Arstilo (8ISC Abstract Proceedings, 2022)
Doing contextual theology has been shared with a massive conversation, discussion, and fluctuation. The world civilization requires instant transformation, which encourages the church to reformulate and reconstruct its theology to be hospitable and engaging with current issues. Pandemic covid-19 contributes alterations to the church. It leads Christians to rethink how to express and reflect their theological identity in the new normal era. It challenges religion to display its values that could benefit the world. Christian theology, however, offers alternative expressions that possibly donate constructive notions to the tension. An inappropriate approach dangers Christian theology purity; further, it leads to hermeneutics malpractice, fatalism, and apatheticsm. In response, it is essential to express the core and heart of theology adequately. This research attempts to analyze and reconstruct how Christians reflect their theological identity toward pandemic covid-19. The qualitative approach leads this project with supporting literature such as books, articles, and other related references. Eventually, the theodicy-preventive approach offers alternative notions to express Christian dogmatic and theology identity. Keywords : theodicy-preventive approach, contra fatalism, Covid-19, theology